2017
DOI: 10.3389/fmolb.2017.00063
|View full text |Cite
|
Sign up to set email alerts
|

Agonist Binding to Chemosensory Receptors: A Systematic Bioinformatics Analysis

Abstract: Human G-protein coupled receptors (hGPCRs) constitute a large and highly pharmaceutically relevant membrane receptor superfamily. About half of the hGPCRs' family members are chemosensory receptors, involved in bitter taste and olfaction, along with a variety of other physiological processes. Hence these receptors constitute promising targets for pharmaceutical intervention. Molecular modeling has been so far the most important tool to get insights on agonist binding and receptor activation. Here we investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
70
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(73 citation statements)
references
References 183 publications
(329 reference statements)
2
70
0
1
Order By: Relevance
“…Por un lado se estudió la unión de los ligandos GABA, muscimol, bicuculina y gabazine Una vez clasificados los aminoácidos se computaron dosíndices estadísticos: precisión y sensibilidad, que han sido empleados en trabajos para evaluar la calidad de modos de unión obtenidos computacionalmente [237][238][239][240][241].…”
Section: Métodosunclassified
“…Por un lado se estudió la unión de los ligandos GABA, muscimol, bicuculina y gabazine Una vez clasificados los aminoácidos se computaron dosíndices estadísticos: precisión y sensibilidad, que han sido empleados en trabajos para evaluar la calidad de modos de unión obtenidos computacionalmente [237][238][239][240][241].…”
Section: Métodosunclassified
“…Unfortunately, the average sequence identity between these chemosensory hGPCR targets and the hGPCR templates with available experimental structural information is invariably 20% or lower [23,109], making bioinformatics/docking-based structural predictions far from trivial [9,10,12,13,[123][124][125][126][127]. Indeed, predictions of agonist binding to bitter taste and olfactory receptors using a variety of docking approaches showed that their predictive power is very limited [23], as they are not able to capture the residues shown experimentally to be important for binding. These initial binding poses can be further refined with MD simulations, in particular using our MM/CG approach, resulting in a dramatic improvement in the predictions [23,128,129].…”
Section: Applications To Human G-protein Coupled Receptorsmentioning
confidence: 99%
“…Indeed, predictions of agonist binding to bitter taste and olfactory receptors using a variety of docking approaches showed that their predictive power is very limited [23], as they are not able to capture the residues shown experimentally to be important for binding. These initial binding poses can be further refined with MD simulations, in particular using our MM/CG approach, resulting in a dramatic improvement in the predictions [23,128,129].…”
Section: Applications To Human G-protein Coupled Receptorsmentioning
confidence: 99%
See 2 more Smart Citations